Posted by **Kjd** on Thursday, May 17, 2012 at 7:10pm.

Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why the graph of (fxg)(x) is equivalent to the graph of h(x)=cos x after it has been horizontally compressed by a factor of 1/2. Please help, thank you!

- trig function -
**Reiny**, Thursday, May 17, 2012 at 7:46pm
(fxg)(x) = (cosx - sinx)(cosx + sinx)

= cos^2 x - sin^2 x

= cos 2x , by definition.

notice the period of the new one is 2π/2 = π

while the period of the first one was 2π

notice the compression by a factor of 1/2 ?

- trig function -
**Kjd**, Thursday, May 17, 2012 at 7:56pm
Oh your right! Now I see that, thanks so much!

## Answer This Question

## Related Questions

- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig and combine function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- trig - The expression 4 sin x cos x is equivalent to which of the following? (...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- tigonometry - expres the following as sums and differences of sines or cosines ...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- trig - I dont understand this. can you please tell how you got each answer? ...

More Related Questions